Removal of Boron from Simulated Iraqi Surface Water by Electrocoagulation Method (Journal of Engineering, 2012)
The removal of boron from aqueous solution was carried out by electrocoagulation (EC) using magnesium electrodes as anode and stainless steel electrodes as cathode. Several operating parameters on the removal efficiency of boron were investigated, such as initial pH, current density, initial boron ion concentration, NaCl concentration, spacing between electrodes, electrode material, and presence of carbonate concentration. The optimum removal efficiency of 91. 5 % was achieved at a current density of 3 mA/cm² and  pH = 7 using (Mg/St. St. ) electrodes, within 45 min of operating time. The concentration of NaCl was o. 1 g/l with a 0.5cm spacing between the electrodes. First and second order rate equation were applied to study adsorption kinetics. The adsorption process follows second order kinetic model with good correlation. The energy consumption was evaluated for the optimum operating conditions. It was in the range of 1.296 to 1.944 Kwh/m3 . The overall expected increase in the operating cost of water treatment using membrane desalination facility (for example) will be about 20%.